Genomics-assisted breeding for boosting crop improvement in pigeon pea (Cajanus cajan) - Pazhamala, Lekha; Saxena, Rachit K.; Singh, Vikas K.; Sameerkumar, C.V.; Kumar, Vinay; Sinha, Pallavi; Patel, Kishan; Obala, Jimmy; R.Kaoneka, Seleman; Tongoona, P.; Shimelis, Hussein A.; Gangarao, N.V.P.R.; et al. (Frontiers in plant science, 2015)
Pigeon pea is an important pulse crop grown predominantly in the tropical and sub-tropical regions of the world. Although pigeon pea growing area has considerably increased, yield has remained stagnant for the last six decades mainly due to the exposure of the crop to various biotic and abiotic constraints. In addition, low level of genetic variability and limited genomic resources have been serious impediments to pigeon pea crop improvement through modern breeding approaches. In recent years, however, due to the availability of next generation sequencing and high-throughput genotyping technologies, the scenario has changed tremendously. The reduced sequencing costs resulting in the decoding of the pigeon pea genome has led to the development of various genomic resources including molecular markers, transcript sequences and comprehensive genetic maps. Mapping of some important traits including resistance to Fusarium wilt and sterility mosaic disease, fertility restoration, determinacy with other agronomically important traits have paved the way for applying genomics-assisted breeding (GAB) through marker assisted selection as well as genomic selection (GS). This would accelerate the development and improvement of both varieties and hybrids in pigeon pea. Particularly for hybrid breeding programme, mitochondrial genomes of cytoplasmic male sterile (CMS) lines, maintainers and hybrids have been sequenced to identify genes responsible for cytoplasmic male sterility. Furthermore, several diagnostic molecular markers have been developed to assess the purity of commercial hybrids. In summary, pigeon pea has become a genomic resources-rich crop and efforts have already been initiated to integrate these resources in pigeon pea breeding.
Keywords: Pigeonpea; Genetic variability; Genomic resources; Genomics-assisted breeding; Marker assisted selection; Genomic selection